Examining Causality Effects On Stock Returns, Foreign Equity Inflow, and Investor Sentiment: Evidence From Indonesian Islamic Stocks - Ansari, Rizal; Al Hashfi, Umar; Setiyono, Bowo (UI Scholars Hub, 2020)
Our study aims to examine the relation of stock return, foreign equity inflow, and investor sentiment in Indonesian Islamic stocks. We use monthly data from 2012 to 2018 and 109 firms with 9,156 total observations. Considering heterogeneity and endogeneity assumption, our models are estimated by the system generalized method of moment. Our research found a positive bi-directional effect between stock return and investor sentiment on the contemporaneous period and the uni-directional effect in which investor sentiment negatively impacts stock return. Our research also found a between stock return and foreign investor inflow. Last but not least, those imply to asset pricing, trading strategy, and portfolio management in Islamic shares.